A study on the effect of nano-precipitates on fracture behavior of nano-structured Al-2wt%Cu alloy fabricated by accumulative roll bonding (ARB) process - Azad, Bahram; Borhani, Ehsan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
An Al-2wt%Cu alloy was subjected to accumulative roll bonding (ARB) process up to a strain of 4.8. The two kinds of different microstructures, i.e, solution treated (ST) one and 190°C pre-aged for 30min (Aged), were prepared as the starting structures for the ARB process. The microstructures were studied by transmission electron microscope (TEM) and electron backscattering diffraction (EBSD). The results showed that the fine precipitates having the average particle size of 16 nm were formed after aging process. On the other hand, the mean grain size of the ST-ARB and the Aged-ARB specimens reached to 650 nm and 420 nm, respectively. Study of the fracture surfaces were carried out by scanning electron microscope (SEM). The results indicated that at 0-cycle ARB, the specimens show dimples indicating the micro-void coalescence (MVC) mechanism of ductile fracture. The average size of dimples was larger in the ST-ARB specimen compared to the Aged-ARB specimen. The fracture mode was transgranular cleavage fracture in the Aged-specimen. At 3-cycle and 6-cycle ARB, the specimens also showed cleavage facets and river lines, that the river lines or the stress lines are steps between cleavage or parallel planes, which are always converged in the direction of local crack propagation.